The brown body as thirdspace: Ta-Nehisi Coates "Between the World and Me" - Zeeuw, Diane (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Edward Soja`s work regarding spatial understanding has become key to discerning a radical shift in the way we frame and then reason about otherness, and more specifically, exclusion. But rather than viewing otherness and exclusion as merely the result of relationships reproduced within our "environment", author and political analyst Ta-Nehisi Coates suggests that it is the vulnerable black or brown body that has historically been the site for the violent performance of racism.
Keywords: racism; thirdspace; body; justice